Odpowiedzi

2010-03-24T19:22:19+01:00
2x+3=2 - przenosisz 3 na drugą stronę
13x-2y=13

2x=-1 |:2
13x-2y=13

x=-0,5
13*(-0,5)-2y=13 - podstawiasz za x -0,5

x=-0,5
-6,5-13=2y - przeniosłam 2y na drugą stronę, 13 też na drugą ;)

x=-0,5
-19,5=2y |:2

x=-0,5
y=-9,75
2010-03-24T19:23:00+01:00
2x=2-3
2x=-1 /:2
x=-0,5

13*(-0,5)-2y=13
-6,5-2y=13
-2y=6,5+13
2y=19,5
y=9.75
:)
2010-03-24T20:09:21+01:00
2x+3=2
13x-2y=13

2x=2-3
13x-2y=13

2x=-1/:2
13x-2y=13

x=-0,5
13*(-0,5)-2y=13

x=-0,5
-6,5-2y=13

x=-0,5
-2y=13+6,5

x=-0,5
-2y=19,5/:(-2)

x= -0,5
y=-9,75